Facets of at Paris Descartes University: Which role for faculty members? The case of the PRISMES project - Parchemal, Yannick; Baron, Georges-Louis (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2023)
In higher education, e learning covers a wide spectrum of situations, with three common requirements: the delivery of pertinent on-line resources, adequate human support to learners and the involvement of faculty members. This text presents a case study about an “experimental” project led at Université Paris Descartes (PRISMES) that has aimed at conjugating those three aspects. Overall, the main lesson learnt confirms that, in a context of high expectations from authorities regarding a quick return on investment, things are much more complex and that results crucially depend not only upon the involvement of a few innovators but, more fundamentally, on the mobilization of a network of actors.